DNA methylation at promoter regions regulates the timing of gene activation in xenopus laevis embryos - El Maarri, Osman (2002)
The levels of genomic DNA methylation in vertebrate species display a wide range of developmental dynamics. Here, we show that in contrast to mice, the paternal genome of the amphibian, Xenopus laevis, is not subjected to active demethylation of 5-methyl cytosine immediately after fertilization. High levels of methylation in the DNA of both oocyte and sperm are maintained in the early embryo but progressively decline during the cleavage stages. As a result, the Xenopus genome has its lowest methylation content at the midblastula transition (MBT) and during subsequent gastrulation. Between blastula and gastrula stages, we detect a loss of methylation at individual Xenopus gene promoters (TFIIIA, Xbra, and c-Myc II) that are activated at MBT. No changes are observed in the methylation patterns of repeated sequences, genes that are inactive at MBT, or in the coding regions of individual genes. In embryos that are depleted of the maintenance methyltransferase enzyme (xDnmt1), these developmentally programmed changes in promoter methylation are disrupted, which may account for the altered patterns of gene expression that occur in these embryos. Our results suggest that DNA methylation has a role in regulating the timing of gene activation at MBT in Xenopus laevis embryos.